A Molecular Mechanics Conformational Study of Peptide T - Godjayev, Niftali M.; Akverdieva, G.; AKYÜZ, SEVİM (Elsevier, 1997)
Conformational behaviour of peptide T, a competitor of the human immuno-deficiency virus in the binding to human T cells, was investigated by theoretical conformational analysis. Two types of conformations are found to be the most stable: quasi cyclic conformation, which is favourable for intensive electrostatic interaction between the charged terminal groups, and spiral conformation, which provides optimal nonvalent interaction of atoms of the polypeptide skeleton. A β-turn of the polypeptide chain was revealed on the section Thr4-Tyr7.
Keywords: Theoretical conformational analysis; Amino acid residue; Peptide